Serial analyses of clinical spectra and outcomes in Chinese women with pregnancy-induced optic neuritis - Bai, Wenhao; Sun, Mingming; Song, Honglu; Li, Hongen; Xu, Xintong; Chen, Xiyun; Zhao, Yixuan; Chen, Biyue; Yao, Sheng; Xu, Quangang; Wei, Shihui; Zhou, Huanfen; et al. (Frontiers in Medicine, 2022)
Objective: To investigate the clinical spectrums and outcomes in pregnancy-related optic neuritis (ON). Methods: We analyzed the clinical subtype and prognosis of women with pregnancy-related ON in the neuro-ophthalmology department of the First Medical Centre at the Chinese PLA General Hospital from January 2014 to December 2019. Results: A total of 54 patients, including 21 (38.9%) idiopathic ON (ION), 27 (50.0%) aquaporin-4 (AQP4)-ON and 6 (11.6%) myelin oligodendrocyte glycoprotein (MOG)-ON patients, who experienced 58 informative pregnancies and 67 episodes of pregnancy-related ON were assessed. Among the ON attacks, there were 11 (16.4%) during pregnancy and 56 (83.6%) within 1 year postpartum(PP1) or after abortion, including 33 (49.3%) in the first trimester. Fourteen (25.9%) patients with ON onset before pregnancy had a higher relapse rate during PP1 than within 1 year before pregnancy (p=0.021). Twenty-four (85.7%) eyes with ION and nine (100%) with MOG-ON had significantly better visual outcomes (p≥0.5) than those with AQP4-ON (14, 35%) (p<0.001 and p<0.001, respectively). Two AQP4-ON patients respectively had a premature birth and a low baby weight. There were no birth defects or stillbirths. Conclusion: The significantly increased relapse rate and numerous cases of ON after pregnancy suggest that delivery adversely affects ON course.